2010
DOI: 10.1099/jmm.0.022319-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of antimicrobial resistance in non-typhoidal salmonellae associated with systemic manifestations from India

Abstract: Extended-spectrum cephalosporins and fluoroquinolones are essential antimicrobials for treating invasive salmonellosis, although emerging resistance to these antimicrobials is of growing concern, especially in India. Therefore, a study was conducted to characterize the antimicrobial susceptibility phenotypes, types of extended-spectrum b-lactamase (ESBL) gene plasmids and serological relationships of 21 non-typhoidal Salmonella isolates from patients who attended three different hospitals in India from 2006 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 35 publications
4
42
1
2
Order By: Relevance
“…Another report has documented the isolation of S. Worthington and S. Weltevreden from neonatal sepsis cases from Pune and South India, respectively (Muley et al, 2004;Patil et al, 2006). In Pondicherry, S. Agona and S. Typhimurium have been isolated from adult patients complaining of diarrhoea and fever (Menezes et al, 2010). So far, to the best of our knowledge, this is the first report from India of human bacteraemia caused by S. Choleraesuis, in which isolates were recovered both from blood and urine samples.…”
Section: Discussionmentioning
confidence: 85%
“…Another report has documented the isolation of S. Worthington and S. Weltevreden from neonatal sepsis cases from Pune and South India, respectively (Muley et al, 2004;Patil et al, 2006). In Pondicherry, S. Agona and S. Typhimurium have been isolated from adult patients complaining of diarrhoea and fever (Menezes et al, 2010). So far, to the best of our knowledge, this is the first report from India of human bacteraemia caused by S. Choleraesuis, in which isolates were recovered both from blood and urine samples.…”
Section: Discussionmentioning
confidence: 85%
“…Variable percentage resistance for third generation cephalosporins was reported from China (1.6%), Romania (11.4%) and the US (16%) [5,6,17]. This emerging resistance to fluoroquinolones and third generation cephalosporins is alarming since these are the current drugs of choice for treating invasive salmonellosis in humans [24][25][26][27].…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…MDR S. Senftenberg isolated from goat meat showed resistance to both fluoroquinolones (MIC of ciprofloxacin: >32 µg/mL; ofloxacin: >32 µg/ mL; norfloxacin: >256 µg/mL) and third generation cephalosporins (MIC of cefotaxime: >256 µg/mL; ceftriaxone: >256 µg/mL and ceftazidime: 16 µg/ mL) ( Table 2). NTS serovars like S. Agona, S. Choleraesuis, S. Enteritidis and S. Typhimurium showing resistance to both these groups of drugs is on a rise and have been reported from other countries including India [24][25][26][27].…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…An estimate of the burden of NTS disease in South Asia extrapolated from a single study of returning travelers to Sweden suggested an incidence of 470 per 100,000 personyears, 3 but that number is likely not representative of the incidence within the local population. Most reports from South Asia have been limited to surveillance of antimicrobial resistance patterns 4,5 and circulating serotypes. 6 Studies on the burden of illness and risk factors for disease are limited.…”
Section: Introductionmentioning
confidence: 99%